Manuel des frontières linguistiques dans la Romania - Ossenkop, Christina; Winkelmann, Otto, 1949- (Manuals of romance linguistics ;, 2018)
"This manual presents an overview of research on language boundaries in Romance-speaking areas both in and outside of Europe. It considers sociolinguistic and psycholinguistic aspects as well as matters of language policy and language geography. The main focus lies on the current boundaries between Romance languages and between Romance and neighboring languages"--